2015
DOI: 10.1089/gtmb.2014.0261
|View full text |Cite
|
Sign up to set email alerts
|

Contribution ofeNOSVariants to the Genetic Susceptibility of Coronary Artery Disease in a Tunisian Population

Abstract: Nitric oxide (NO), produced by the enzyme endothelial nitric oxide synthase (eNOS), has critical roles in the regulation of vascular homeostasis and prevention of atherogenesis by inhibiting leukocytes, platelet activation, and smooth muscle cell proliferation. There is strong experimental and clinical evidence that abnormalities in eNOS availability play an important role in the pathophysiology of coronary artery disease (CAD). Controversial results regarding the association of eNOS gene polymorphisms with CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…This remained significant after adjustment for age, gender, diabetes, smoking, and hypertension. These findings suggest that the G894T (rs1799983) polymorphism of the NOS3 was associated with CAD in Tunisian patients (Ben Ali et al, 2015). In our study, the difference in the distribution of genotype frequencies of rs1799983 between CAD subjects and healthy controls was significant.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This remained significant after adjustment for age, gender, diabetes, smoking, and hypertension. These findings suggest that the G894T (rs1799983) polymorphism of the NOS3 was associated with CAD in Tunisian patients (Ben Ali et al, 2015). In our study, the difference in the distribution of genotype frequencies of rs1799983 between CAD subjects and healthy controls was significant.…”
Section: Discussionsupporting
confidence: 47%
“…Genetic studies have consistently demonstrated a substantial genetic influence on the development of CAD, with inherited risk estimates in the range 20-60% (Kraus, 2000;Won et al, 2015;Yamada et al, 2015). Other studies have suggested that polymorphisms in the enzyme endothelial nitric oxide synthase (NOS3) may relate to CAD (Ben Ali et al, 2015;Gaunt and Davey Smith, 2015;Shim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These inconsistencies may be linked to the African population’s high genetic diversity and low levels of linkage disequilibrium among loci when compared to populations from other countries outside Africa [ 105 ]. Furthermore, studies suggest that from a genetic standpoint, there is no SNP-database that can be used to personalize treatments for HTN in an African population [ 47 , 106 , 107 ]. Inferring that the lack of genetic information with robust allele frequency distributions serves as a hurdle to implement corrective treatment and this may have important medical implications [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, these factors are consistently and independently related to CAD. 30 32 The evidence is based on numerous prospective epidemiological studies and clinical observations in the general population. 33,34 Our previous study explains the pathophysiology mechanisms of diabetes, hypertension, and dyslipidemia in the contribution of CAD.…”
Section: Discussionmentioning
confidence: 99%